A new subspecies of Xestia ashworthii (Doublebay, 1855) from Russian Altai (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Dvořák, Marek (Zootaxa, 2016)
Xestia Hübner, [1818] is a large noctuine genus with an almost worldwide distribution. In the Palaearctic region the genus represented by about 190 described species (Kononenko 2003; Gyulai & Ronkay 2006; Fibiger et al. 2010; Gyulai et al. 2011; Kononenko et al. 2012; Gyulai et al. 2013a; 2013b). The genus subdivided into four described subgenera (Lafontaine et al. 1998, in Lafontaine 1998; Kononenko et al. 2012): Xestia, Megasema Hübner, [1821], Pachnobia Guenée, 1852 (= Schoyenia Aurivillius, 1883; Anomogyna Staudinger, 1871) and Raddea Alphéraky, 1892 (= Estimata I. Kozhanchikov, 1928; Erebophasma Boursin, 1963). Schoyenia and Anomogyna have been synonymised with Pachnobia by Lafontaine et al. (1998, in Lafontaine 1998). On the status of Raddea and synonymy of Estimata and Erebophasma see Lafontaine (1998). The genus is most diverse in the mountains of South Siberia, West China and the Himalayas. The Holarctic taxa of Pachnobia were revised by Mikkola et al. (1983, as Schoyenia), Lafontaine et al. (1987, as Pachnobia), and Lafontaine et al. (1998, in Lafontaine 1998); European taxa of the genus have been reviewed by Fibiger (1992; 1997), and the Nearctic fauna has been revised by Lafontaine (1998). The Asiatic fauna of the genus needs revision.